THE USE OF CODE-SWITCHING BY ENGLISH TEACHERS IN VOCATIONAL HIGH SCHOOL - Kirana, Haritsah Ayu; Muhayyang, Maemuna; Radhiyani, Fitri (Universitas Negeri Makassar, 2025)
The purpose of this research is to identify the types and functions of code-switching that English teachers employ. The descriptive qualitative method was used to gain the data. This research was conducted at SMK Negeri 6 Makassar at the X Culinary Art 1 and X Cosmetology 1. The data were collected from observation and interviews with the teachers. Based on the research’s findings, English teachers in vocational high school used code-switching in 80 cases. The researcher discovered that (1) intra-sentential code-switching was the most common type, and (2) teachers mostly used code-switching to manage the class by questioning students about related material to keep them focused or giving instructions to do activities. Therefore, it may be concluded that code-switching can encourage students to use English more often and is considered an effective strategy in the English classroom.